The issue of the development of the preamble to the armenian constitution: from theory to practice - Manasyan Anahit (Revista Institutului Naţional de Justiţie, 2019)
The article considers the issues of axiological characteristics of constitutional preambles and possibilities of their amendment. The author concludes that the constitutional preamble, besides the declaratory significance, has a constitutional value, practical importance. The unchangeability of the constitutional preamble, its citation among the unchangeable constitutional articles and other circumstances with regard to this are conditioned by the contentual peculiarities of the preamble and are subject to assessment in each concrete situation. The Armenian constitutional preamble should be unchangeable from the textual viewpoint. At the same time, it can be developed via other alternative ways, having as a key point the circumstance that the above-mentioned regulations are subject to dynamic interpretation, within the frames of which changes of perception of their separate elements are possible, simultaneously, the elements, constituting the „core”, „kernel” of these principles, should be unchangeable.